Account Manager PT Abbauf Mulia Konsultan Teknologi - Azizah, Rahayu Zahrotul; Susanto, Yulius Kurnia; Wijaya, Novia; Supriatna, Dicky (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This final internship report is a form of accountability to provide an explanation regarding the author's activities while undergoing an internship at PT Abbauf Mulia Konsultan Teknologi, which was organized through the Merdeka Campus Certified Internship program for work programs from the Government Ministry of Education, Culture, Research, and Technology. PT Abbauf Mulia Konsultan Teknologi is a consulting company engaged in technology. The contents of this report describe the routine activities and responsibilities as an apprentice placing the account manager position in the “Management of Marketing Strategy by Account Manager for Grouping Target Clients of GIS Products” project. The author explains the benefits and experience in the world of work, especially related to the analysis of market materials and product analysis from PT Abbauf Mulia Konsultan Teknologi.